1997
DOI: 10.1093/brain/120.12.2251
|View full text |Cite
|
Sign up to set email alerts
|

Evolving isolated hand palsy: a parietal lobe syndrome associated with carotid artery disease

Abstract: Six patients with cerebral ischaemia who presented evolving isolated hand palsy were studied, five prospectively and one retrospectively. The motor deficit involved only the hand and the wrist in some cases. In almost all cases the motor deficit was pseudo-ulnar. None of them had a Babinski sign, all had mild sensory symptoms or signs in the affected hand. CT and MRI disclosed recent infarctions contralateral to the affected hand, in the white matter of the angular gyrus, in a vascular borderzone. Five had a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 14 publications
3
35
1
1
Order By: Relevance
“…9 Timsit et al first reported evolving isolated hand palsy as a parietal lobe syndrome in six patients with associated carotid disease. 10 In his series, all patients had pure motor pseudo-ulnar deficits without sensory or pyramidal tract signs, which were localized to infarction of the angular gyrus of the inferior parietal lobe.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…9 Timsit et al first reported evolving isolated hand palsy as a parietal lobe syndrome in six patients with associated carotid disease. 10 In his series, all patients had pure motor pseudo-ulnar deficits without sensory or pyramidal tract signs, which were localized to infarction of the angular gyrus of the inferior parietal lobe.…”
mentioning
confidence: 96%
“…Cortical-based lesions that produce a syndrome of distal arm or hand paresis have been reported from France, Germany, Japan, and Korea. [10][11][12][13][14] We present 35 North American cases of one-arm stroke, the largest series of its kind, and provide topographical cortical mapping of these lesions.…”
mentioning
confidence: 99%
“…This may imply that disruption of cortical influences other than the primary motor cortex could be responsible for some of the impairment in tongue function in cortical and large subcortical lesions. Timsit et al [20]described isolated motor deficits of the hand following parietal lobe infarctions in 6 patients. Similarly dysfunction in cortical areas other than the precentral gyrus (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Sıklıkla periferal lezyon lehine yanlış tanı almaktadır. Büyük arter aterosklerozuna bağlı gelişen motor korteksteki fokal infarkt izole el güçsüzlüğüne neden olabilir (1)(2). Radial sinirin kompresyon ve travma başta olmak üzere çeşitli nedenlerle zarar görmesi sonucunda bu sinirin felci ve düşük el meydana gelir (3).…”
Section: Introductionunclassified